1981
DOI: 10.1017/s003329170005282x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical anorexia nervosa

Abstract: SYNOPSISThe Eating Attitudes Test (Garner & Garfinkel, 1979) was administered to 578 students (446 females and 132 males) at a College of Technology and to 14 ‘control’ subjects fulfilling diagnostic criteria for anorexia nervosa. Although no male students scored highly, a total of 28 female students (6·3% of the female student sample) scored in the ‘anorexic’ range. These ‘high scorers’, together with a random control group of 28 ‘non-high scorers’, were subsequently Interviewed. Interview revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
2
7

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(174 citation statements)
references
References 11 publications
9
156
2
7
Order By: Relevance
“…The validity studies were conducted on samples of populations considered to be at higher risk for eating disorders, in which the possibility to detect disease cases was elevated (9)(10)(11)(12)14,16). This could consequently yield a higher positive predictive value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity studies were conducted on samples of populations considered to be at higher risk for eating disorders, in which the possibility to detect disease cases was elevated (9)(10)(11)(12)14,16). This could consequently yield a higher positive predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the EAT has been widely used both in its complete and its short version (7), although, to date, few studies have been conducted to assess its psychometric properties (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first studies we found in this vein was published in 1987 and observed a rise in the number of first-time psychiatric admissions in England, between 1972 and1981. From the authors' analysis of the age-period-cohort effect, Williams and King (1987) concluded that this was not a significant increase in cases of AN.…”
Section: Indicators Against the Increase Of Anmentioning
confidence: 91%
“…The different food intake and preferences by males and females may be related to such influences as cultural habits or fashion. As is the custom, females take much less food than males, eat less meat (FIDDES 1991) and limit the energy value of food (BUTTO & WHITEHOUSE 1991). Females usually have more pronounced aversions against many kinds of food (PILGRIM 1957).…”
Section: Influence Of Sexmentioning
confidence: 99%